Peroxisomes and Golgi apparatus as players in Ca2+ homeostasis - Pizzo, Paola; Costa, Alex (Henry Stewart Talks, 2013)
Role of Peroxisomes and Golgi apparatus within the cell, Methodologies to study peroxisomal and Golgi apparatus Ca2+ signals, Ca2+ handling by mammalian and plant peroxisomes and its functional role, Differential Ca2+ homeostasis in sub-regions of the Golgi apparatus and functional roles
Reviewed at 2019/11/22